2015
DOI: 10.1002/jhet.2468
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and in vitroAntimicrobial Activity of Nalidixic Acid Hydrazones

Abstract: A series of nalidixic acid‐based hydrazones have been synthesized and evaluated for their in vitro antimicrobial activity using the broth microdilution method against a panel of reference strains of microorganisms, including Gram‐positive bacteria, Gram‐negative bacteria, and fungi belonging to yeasts Candida spp. and molds Aspergillus spp., Penicillium spp., and Rhizopus spp. Nalidixic acid derivatives were obtained by condensation reaction of nalidixic acid hydrazide with substituted (hetero)aromatic aldehyd… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
10
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
8

Relationship

6
2

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 19 publications
1
10
0
Order By: Relevance
“…It is worth to stress that in our previous research, hydrazide–hydrazones of substituted benzoic acids showed significant activity against Gram‐positive bacteria . In particular, N ‐[(2‐hydroxy‐3,5‐diiodophenyl)methylidene]‐3‐methoxybenzhydrazide displayed activity much higher than commonly used chemotherapeutics against Bacillus spp . The above‐mentioned findings further support the growing importance of the synthesis of hydrazide–hydrazones derivatives.…”
supporting
confidence: 73%
See 1 more Smart Citation
“…It is worth to stress that in our previous research, hydrazide–hydrazones of substituted benzoic acids showed significant activity against Gram‐positive bacteria . In particular, N ‐[(2‐hydroxy‐3,5‐diiodophenyl)methylidene]‐3‐methoxybenzhydrazide displayed activity much higher than commonly used chemotherapeutics against Bacillus spp . The above‐mentioned findings further support the growing importance of the synthesis of hydrazide–hydrazones derivatives.…”
supporting
confidence: 73%
“…Recently, we reported interesting results concerning the synthesis and antibacterial activity of hydrazide–hydrazones . It is worth to stress that in our previous research, hydrazide–hydrazones of substituted benzoic acids showed significant activity against Gram‐positive bacteria .…”
mentioning
confidence: 86%
“…Furthermore, recently we have reported interesting studies concerning the antimicrobial activity of hydrazide–hydrazones . A significant antibacterial activity, with greater efficacy than commonly used antibiotics, was observed with nitrofurazone analogues containing hydrazide–hydrazone moiety .…”
Section: Introductionmentioning
confidence: 99%
“…In our previous articles, we described the synthesis of hydrazide‐hydrazone derivatives which showed significant antibacterial activity. [ ][ ] Particularly some of hydrazide‐hydrazones of 3‐methoxybenzoic acid and 4‐ tert‐ butylbenzoic acid showed higher antibacterial activity than commonly used antibiotics against Bacillus spp . In addition to this hydrazide‐hydrazones of 2‐substituted acetic acids displayed high bactericidal activity against a panel of Gram ‐positive bacterial strains …”
Section: Introductionmentioning
confidence: 99%